1993
DOI: 10.1002/edp.2430020205
|View full text |Cite
|
Sign up to set email alerts
|

Practices and representations of child care and motor development among West Africans in Paris

Abstract: Massage techniques and postural manipulation used by West African women immigrants in Paris were studied, with the aim of demonstrating that culturally regulated caretaking practices have an influence on infant motor development. Twenty-five infants were observed between the ages of 3 and 12 months and 9 and 15 months. Frequency of massage and its accompanying set of physical exercises were found to be related to age at onset of independent walking. The findings show that infants receiving daily massage walk s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The motor development of these infants, like other African infants, is often more advanced at this age (Super, 1976). Body postures are the object of vigorous manipulations, as we have seen in the Wolof massaging customs (Rabain-Jamin & Wornham, 1993) and as other authors have observed in several African societies (Bril & Sabatier, 1986;Super, 1976;Trevarthen, 1988). The verbal counterparts of the mothers' vigorous body practices are found in their highly emphatic verbal requests (consisting essentially of orders and a large range of negatives), which are accompanied by constant attentiveness to the baby's reaction.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The motor development of these infants, like other African infants, is often more advanced at this age (Super, 1976). Body postures are the object of vigorous manipulations, as we have seen in the Wolof massaging customs (Rabain-Jamin & Wornham, 1993) and as other authors have observed in several African societies (Bril & Sabatier, 1986;Super, 1976;Trevarthen, 1988). The verbal counterparts of the mothers' vigorous body practices are found in their highly emphatic verbal requests (consisting essentially of orders and a large range of negatives), which are accompanied by constant attentiveness to the baby's reaction.…”
Section: Discussionmentioning
confidence: 88%
“…The Wolof mothers were contacted during regular visits to a neighbourho od-based health centre in the 20th district of Paris in an area with a high immigrant population. From a larger sample of Western African families in which caretaking practices were studied (Rabain-Jamin & Wornham, 1993), only the four Wolof dyads were considered. The ve French mothers were contacted in another health centre 50 km south of Paris.…”
Section: Methods Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross cultural studies examining the development of locomotion in humans have shown that different rearing practices can lead to different time courses in the onset of walking (Adolph & Robinson, ). For example, in Uganda mothers engage in rearing practices that are intended to facilitate the onset of walking (Bril & Sabatier, ; Hopkins & Westra, ; Rabain‐Jamin & Wornham, ; Super, ). Bouncing, shaking, and rubbing the legs of their infants quickens the onset of motor development with the children walking as early as 7 months of age.…”
Section: Introductionmentioning
confidence: 99%